Role of Pyridine Containing Azetidinone Derivatives as Privileged Scaffolds in Anti Tubercular Agents - N. Pramod; C. Bharath Kumar; P. Sri Lekha; B. Mayuri (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
In search of potential therapeutics for Tuberculosis, in the present research we described herein a novel series of 3-Chloro-1-phenyl-4-(pyridine-4yl-)azetidin-2-one derivatives were synthesized by forming of Schiff base as intermediate. The resulted Schiff base further undergoes elimination to give titled Azetidinone derivatives. The Mechanism Involved in the formation of Schiff base is Nucleophilic addition followed by elimination. The formed Schiff base undergoes further cyclization to give novel Azetedinone derivatives. The titled compounds were characterized physically and analyzed structurally by spectroscopic methods (IR, 1H-NMR, MASS). The compounds Azt-1 to Azt-6 were screened for selected In vitro anti-tubercular activity. In vitro anti-tubercular activity was performed by using the Micro plate Alamar Blue Assay (MABA) method. The most active compounds of the series were Azt-1(H), Azt-2(Cl), Azt-5 (O-OH) and Azt-6 (P-OH) than standards. The Potent anti tubercular activity might be the presence of Electron withdrawing group -Cl, (Azt-2) and Electron Donating substituents -OH at ortho and para position in the phenyl ring of (Azt-5) and (Azt-6) respectively.